Iron Deficiency Anemia in Pregnancy: A Scoping Review on Maternal and Fetal Outcomes, Diagnosis, and Management - Bagaskoro, Haryo Bagaskoro; Putri, Haifa Hasna; Khusni, Willda Arvia Zhafa; Aqilah, Lintang Inas; Louisa Caroline; Alfaati, Metafisika Amalia; Naya, Akbar Zaki; Arif, Muhammad Ridwan; Ahmadi, Bramas Wisnu; Anggraeni, Evrilia; et al. (Journal of Unified Multidisciplinary Practice in Sports, Health, and Medicine, 2026)
Purpose: To synthesize recent evidence on the prevalence, pathophysiology, maternal-fetal consequences, diagnostic challenges, and management of iron deficiency anemia (IDA) in pregnancy. Materials and Methods: This scoping review retrieved articles from PubMed, Scopus, and ScienceDirect published between 2015 and 2025, using the keywords iron deficiency, iron deficiency anemia, and pregnancy. Studies were selected based on relevance to maternal-fetal health outcomes, diagnostic approaches, and management strategies. Result: The findings demonstrate that IDA affects approximately 38% of pregnancies globally, with the highest burden in South Asia and sub-Saharan Africa. Pathophysiological mechanisms involve hepcidin dysregulation, inflammation, and oxidative stress. Maternal consequences include increased risk of postpartum hemorrhage and transfusion, while fetal outcomes include preterm birth, low birth weight, and neurodevelopmental impairment. Diagnostic challenges stem from hemodilution and inflammatory confounders, requiring biomarkers such as serum ferritin and soluble transferrin receptor. Conclusion: IDA remains a major contributor to maternal and perinatal morbidity. Oral iron supplementation is the first-line treatment, but intravenous formulations are essential for severe cases or poor responders. Adherence to international guidelines and improved implementation in low-resource settings are urgently needed.